Deciphering the mediating role of CXCL10 in hypothyroidism-induced idiopathic pulmonary fibrosis in European ancestry: a Mendelian randomization study - Xing, Xiaoming; Zhao, Cong; Cai, Song; Wang, Jing; Zhang, Jing; Sun, Fang; Huang, Mao; Zhang, Lishan (Frontiers in Immunology, 2024)
Background: Idiopathic pulmonary fibrosis (IPF) is a lethal lung disease characterized by progressive fibrosis, leading to impaired gas exchange and high mortality. The etiology of IPF is complex, with potential links to autoimmune disorders such as hypothyroidism. This study explores the relationship between hypothyroidism and IPF, focusing on the mediating role of plasma proteins.Methods: A two-sample Mendelian randomization (MR) approach was employed to determine the impact of hypothyroidism on IPF and the mediating role of 4,907 plasma proteins, all in individuals of European ancestry. Sensitivity analyses, external validation, and reverse causality tests were conducted to ensure the robustness of the findings. Additionally, the function of causal SNPs was evaluated through gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment analyses.The findings suggest that hypothyroidism, through altered plasma protein expression, particularly CXCL10, may contribute to the pathogenesis of IPF. This novel insight highlights the potential of CXCL10 as a therapeutic target in IPF, especially in patients with hypothyroidism. The study emphasizes the need for further research into the complex interplay between autoimmune disorders and IPF, with a view towards developing targeted interventions for IPF management.